Energy Efficient Healthcare Monitoring System using 5G Task Offloading - T Sigwele; A Naveed; M Susanto; M Ali; Y F Hu (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2019)
Healthcare expenses can be significantly reduced, and lives saved byenabling the continuous monitoring of patient health remotely using WirelessBody Sensor Networks (WBSN). However, an energy efficient mobile gateway(e.g. 5G smartphone) is required which moves with the patient in real time toprocess the data from the bio sensors without depleting the battery. Thispaper proposes a 5G based healthcare cardiovascular disease RemoteMonitoring system called 5GREM using Electrocardiogram (ECG) biosensor as a BSN device. The aim is to monitor and analyse the patient’s heartrhythms and send emergency alerts during irregularities to the nearestcaregivers, ambulance or physician to minimize heart attacks and heartfailures while saving energy. Since ECG signal execution is computerintensive, requests from the ECG sensor are either executed locally on thegateway, offloaded to nearby mobile devices or to the 5G edge whileconsidering the battery level, CPU level, transmission power, delays and taskfail rate.